2018
DOI: 10.1111/efp.12438
|View full text |Cite
|
Sign up to set email alerts
|

Decline of Paulownia tomentosa caused by Trametes hirsuta in Serbia

Abstract: Summary During the monitoring of the health status of nurseries and plantations in Serbia, a decline in a 5‐year‐old Paulownia tomentosa plantation was recorded. Trees displayed symptoms of dieback, massive breaking at different positions, the appearance of decay and fungal fruitbodies at the stems. Using standard isolation methods, white colonies with cottony surfaces and regular growth were obtained from the decaying wood samples, and after the oxidation degree analysis, it was determined that these isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
1
2
0
2
Order By: Relevance
“…This indicated the potentially strong ligninolytic activity of strain X-13. The morphological analysis of strain showed that the colony of strain X-13 was milky white with the dense hyphae, and it revealed a thread-like septate mycelium without any reproductive structures (Additional file 2 : Figure S2), which were similar to those of reported Trametes hirsuta genus strains [ 23 , 24 ]. Moreover, the ITS region sequence of strain X-13 (GenBank: MT995079) showed 99% similarity with that of white-rot basidiomycete Trametes hirsuta JL-22-2 according to NCBI BLAST algorithm analysis.…”
Section: Resultssupporting
confidence: 68%
“…This indicated the potentially strong ligninolytic activity of strain X-13. The morphological analysis of strain showed that the colony of strain X-13 was milky white with the dense hyphae, and it revealed a thread-like septate mycelium without any reproductive structures (Additional file 2 : Figure S2), which were similar to those of reported Trametes hirsuta genus strains [ 23 , 24 ]. Moreover, the ITS region sequence of strain X-13 (GenBank: MT995079) showed 99% similarity with that of white-rot basidiomycete Trametes hirsuta JL-22-2 according to NCBI BLAST algorithm analysis.…”
Section: Resultssupporting
confidence: 68%
“…The most well-known phytosanitary problems on Paulownia spp. are witches' broom determined by phytoplasma (Gao et al, 2008), Phytophthora root and collar rot (Aloi et al, 2021), wood decay caused by Trametes hirsuta (Milenkovic et al, 2018) and root-knot nematodes (Skwiercz et al, 2019). Other diseases affecting Paulownia spp.…”
Section: Introductionmentioning
confidence: 99%
“…There is little information on infectious diseases of paulownias and most of those reported so far are caused by fungi and oomycetes [4,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%